The geometric algebra as mediator in teaching factorization and notable products (Revista de Investigaciones Universidad del Quindío, 2017)
One of the challenges of Mathematics Education is to find new strategies that help understanding mathematical concepts that have being taught in a repetitive way. In this research, we pointed out Notable Products and Factorization using a strategy called the Geometrization of Algebra through easy-access didactic aids such as geometric figures. Also, due to the fact that technology is present in our lives every day, there is the need to incorporate strategies that allow students to perform a dynamic and interactive work; and the best way of doing that is implementing a software called: “Geometry of Polynomials” as a teaching and learning strategy of Notable Products and Factorization of second degree polynomials. Such strategy gives a didactic and innovative alternative that helps students to gain a significant learning of these subjects, leaving behind a traditional way of learning and incorporating two facilitation elements like manipulation of concrete materials and the use of a software specially designed for this project. Lastly, we developed a brochure that shows different activities on how to use the concrete material and a manual for the use of that software.
Keywords: Factorization; Geometrization; Didactics; Software